Dramaturgi Personal Branding Andika-Hendrar dalam Membangun Citra Politik Melalui Instagram (Studi Kasus Kontestasi Calon Pilgub Jateng 2024) - Idelia, Rachel Tivara; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This Study analyzes the strategic dramaturgy implemented by the 2024 Central Java Governor candidate pair, Andika Perkasa and Hendrar Prihadi, in building their political image via Instagram. The dramaturgical approach highlights how candidate pairs create a